Application of the Political Economy to Rural Health Disparities - Taylor, Monica M. (SpringerBriefs in Public Health,, 2018)
This thought-provoking monograph analyzes the longstanding political and economic structures underlying entrenched health inequities in rural areas worldwide. Bypassing familiar data on the subject, it critiques existing approaches to why core social determinants of health are underrepresented in rural communities, and synthesizes knowledge from health behaviors to spatial politics to make creative, equitable suggestions for intervention. The author reviews classic economic and current sociopolitical theory to pinpoint governments' decision-making processes behind resource allocation as they translate into poor service access, service quality, and health outcomes. In reply, corrective policy measures are recommended to address these conditions at the root-cause level, in keeping with global goals of improved health for all. Included in the coverage: · Rural health disparities: the political economy. · Rural health disparities: the economic argument. · Social disorganization in rural communities. · Rural health disparities and social disorder: public policy responses. · The political economy: an era of institutional cynicism? With its forceful argument for dealing with a growing but often invisible crisis, Application of the Political Economy to Rural Health Disparities makes a significant text for graduate and undergraduate programs in public and international affairs, planning and public policy, public health, public administration, and economics. Public health and advocacy organizations will also benefit from the book's vision. .